2021
DOI: 10.3390/ijms22073358
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Administration of 5-(3-chlorophenyl)-4-Hexyl-2,4 -Dihydro-3H-1,2,4-Triazole-3-Thione (TP-315)—A New Anticonvulsant Drug Candidate—On Living Organisms

Abstract: About 70 million people suffer from epilepsy—a chronic neurodegenerative disease. In most cases, the cause of the disease is unknown, but epilepsy can also develop as the result of a stroke, trauma to the brain, or the use of psychotropic substances. The treatment of epilepsy is mainly based on the administration of anticonvulsants, which the patient must most often use throughout their life. Despite significant progress in research on antiepileptic drugs, about 30% of patients still have drug-resistant epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 48 publications
(67 reference statements)
1
2
0
Order By: Relevance
“…Thus, based on docking studies it might be concluded that designed s -triazoles 3 and 4 are able to inhibit Nav1.7 through a voltage-sensor trapping mechanism, similar to that depicted for the native antagonist GX-936. What is important, according to HYDE scoring function ( Figure 3 ) the elongation of the N4 alkyl chain from the butyl to the hexyl ( 1 , 2 ) led to an enhanced receptor-ligand interactions, which is consistent with the experimental results [ 17 ], whereas the HYDE scores are not much different between s -triazoles with the methylene and the ethylene linker ( 1 vs. 3 and 2 vs. 4 , respectively). Furthermore, our docking studies confirm that the binding mode of s -triazoles 1 and 2 is generally very similar to that of s -triazoles 3 and 4 , with some exceptions.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, based on docking studies it might be concluded that designed s -triazoles 3 and 4 are able to inhibit Nav1.7 through a voltage-sensor trapping mechanism, similar to that depicted for the native antagonist GX-936. What is important, according to HYDE scoring function ( Figure 3 ) the elongation of the N4 alkyl chain from the butyl to the hexyl ( 1 , 2 ) led to an enhanced receptor-ligand interactions, which is consistent with the experimental results [ 17 ], whereas the HYDE scores are not much different between s -triazoles with the methylene and the ethylene linker ( 1 vs. 3 and 2 vs. 4 , respectively). Furthermore, our docking studies confirm that the binding mode of s -triazoles 1 and 2 is generally very similar to that of s -triazoles 3 and 4 , with some exceptions.…”
Section: Resultssupporting
confidence: 83%
“…According to the literature, compounds possessing 1,2,4-triazole ring in their structures are characterized by high antiepileptic potential [ 10 , 11 , 12 , 13 , 14 ]. Among them, 4-alkyl-5-aryl-1,2,4-triazole-3-thione derivatives express anticonvulsant activity both against tonic–clonic seizures and in an animal model of drug-resistant epilepsy [ 15 , 16 , 17 ]. Mechanistic studies revealed that these compounds could not affect the GABAergic neurotransmission, neither directly nor allosterically; however, they acted as voltage-gated sodium channel ligands in a low micromolar range [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in living organisms, there was neither alteration of hepatic and renal function nor change of hematologic parameters after long-term administration of TP-315. At a concentration similar to the concentration measured in the tested mice, the activities of the enzymes CYP2B6, CYP2D6, CYP3A4, and CYP3A5 were not significantly inhibited by TP-315, although CYP2C19 was [84]. Potential interaction with some marketed ASMs that are substrates of CYP2C19, such as diazepam, phenytoin, and valproic acid, deserves more investigations.…”
Section: -(3-chlorophenyl)-4-hexyl-24-dihydro-3h-124-triazole-3-thion...mentioning
confidence: 72%